PROTECTION OF FICTIONAL CHARACTERS AGAINST FANFICTION ACTIONS AND ITS RELATION TO FAIR USE IN THE PERSPECTIVE OF COPYRIGHT LAW - Ayu Mustika Pamungkas (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
This research aims to investigate the protection of fictional characters within the framework of intellectual property, including copyright, and explore the challenges arising from fanfiction cases in the era of the internet. Through legal analysis, the study delves into the legal regulations governing fictional characters and identifies the potential application of fair use principles to support fanfiction activities that utilize pre-existing fictional characters. The findings provide insights into the legal framework surrounding fictional characters within intellectual property law and its relevance in addressing the evolving landscape of internet culture. Moreover, this research contributes to a deeper understanding of how to safeguard fictional characters while considering freedom of expression and fostering innovation in the realm of creativity. By examining these issues, this study not only sheds light on the legal aspects of protecting fictional characters but also addresses the dynamic interplay between traditional intellectual property concepts and the transformative nature of fan-driven creativity on the internet, ultimately contributing to the ongoing discourse on the regulation of fictional characters in the digital age.